Sensory evaluation of tender beef strip loin steaks of varying marbling levels and quality treatments. (February 2015) - Corbin, C.H.; O'Quinn, T.G.; Garmyn, A.J.; Legako, J.F.; Hunt, M.R.; Dinh, T.T.N.; Rathmann, R.J.; Brooks, J.C.; Miller, M.F.
Abstract: The palatability of tender [Warner-Bratzler shear force values < 33.34 N (3.4 kg)] beef strip loins of 10 different treatments [USDA Prime, High Choice (upper 1/3 Choice), Low Choice (lower 1/3 Choice), Select, Standard, Australian Wagyu, American Wagyu, Holstein Select, Holstein Top Choice (upper 2/3 Choice) and Grass-finished] was evaluated by consumers and a trained flavor panel. In general, tenderness, juiciness, flavor, and overall liking ratings as well as acceptability percentage for each trait, increased with increased fat levels. Moreover, overall liking was highly correlated ( P  < 0.01) with flavor liking ( r  = 0.96) as well as fat percentage ( r  = 0.79). Beef flavor scores were positively associated ( P  < 0.01) with fat-like ( r  = 0.67) and umami ( r  = 0.59) flavors. Fat level was the primary driver of beef flavor acceptability in all samples when no undesirable off-flavors were present.